A comunicação do ambiente de varejo popular sob a influência da sedução estética : percepções sobre a rede lojas Marisa - Reis, Luciana Braun (2012)
Popular retail communication in the perspective of reception by common people, taking in consideration the influence of the aesthetic seduction of such communication in the Point of Sale. The methodology used is the Comprehensive Sociology (Michel Maffesoli). The techniques used to analyze the object of study are mainly Bibliographical Research, Participant Observation. The epistemological connection constructs the researcher s point of view, with the Comprehensive Sociology preceding the notions Hedonism, regarding consumption, popular consumption, and habits referring to common people. Such notions will be used to analyze the object of study: Lojas Marisa.